Blending Catholicism with Chi, Chakras and Crystals: Research on the Lived Reality of Catholicism Among Pre-Service Postgraduate Student Teachers In Catholic Third-Level Colleges in the Republic of Ireland (ROI) - Kieran, Patricia; Mullally, Aiveen (Brill, 2022)
This article presents the findings of a two-year research project investigating four hundred third-level Initial Teacher Education (ITE) students’ perceptions of the religiously unaffiliated in Ireland. The research was undertaken in two Third Level Catholic colleges of education in the Republic of Ireland. A brief overview of some contemporary cultural, educational and ecclesial factors impacting on participants’ lived experiences and perceptions of Catholicism is provided. Irish society is changing rapidly and the religiously unaffiliated are the fastest growing belief group in the 2016 Census (CSO 2016). A major part of the research focused on the religious or belief affiliation of the sample group. It explores how their personal religious and belief perspectives impact on their own lives as well as their understandings of their future professional roles as educators in Ireland’s primary school system. Drawing on the research survey and interview data the article explores participants’ belief fluidity as it analyses what their experiences might reveal about lived Catholicism in the contemporary Irish context.
Keywords: Lived Catholicism; Ireland; Belief Fluidity; Initial Teacher Educators